Prostaglandin F2α and GnRH administration improved progesterone status, luteal number, and proportion of ovular and anovular dairy cows with corpora lutea before a timed artificial insemination program - Pulley, Stephanie Leeann; Mellieon, H.I. Jr.; Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2012)
The objective of this research was to increase the proportion of cows with at least 1 functional corpus luteum (CL) and elevated progesterone at the onset of the timed artificial insemination (TAI) program. Postpartum Holstein cows in 1 herd were stratified by lactation number at calving (September 2009 through August 2010) and assigned randomly to 1 of 2 treatments: (1) Presynch-10 (n = 105): two 25-mg injections of prostaglandin F2α (PG) 14 days apart (Presynch); and (2) PG-3-G (n = 105): one 25-mg injection of PG 3 days before 100 μg gonadotropin- releasing hormone (GnRH; Pre-GnRH), with the PG injection administered at the same time as the second PG in the Presynch-10 treatment. Cows were enrolled in a TAI protocol (Ovsynch; injection of GnRH 7 days before [GnRH-1] and 56 hours after [GnRH-2] PG with AI 16 to 18 hours after GnRH-2) 10 days after the second or only PG injection. Blood samples for progesterone or estradiol analyses were collected on median days in milk (DIM): 36, 39, 50, 53 (Pre-GnRH), 60 (GnRH-1), 67 (PG), 69 (GnRH-2), and 70 (TAI). Ovarian structures were measured by ultrasonography on median DIM 53, 60, 67, 69, and 6 days post-TAI to determine follicle diameters, ovulation response to GnRH, or both. Although progesterone concentration did not differ between treatments before Pre-GnRH injection, the proportion of cows with at least 1 CL tended to be greater for PG-3-G than Presynch-10 cows, and more PG- 3-G cows ovulated after Pre-GnRH than ovulated spontaneously in Presynch-10. Furthermore, diameter of follicles that ovulated tended to be smaller in PG-3-G than Presynch-10 cows after Pre-GnRH. At GnRH-1, the proportion of cows with progesterone ≥1 ng/mL, the number of CL per cow, and the proportion of cows with at least 1 CL were greater for PG-3-G than Presynch-10. Neither follicle diameter nor percentage of cows ovulating after GnRH-1 differed between treatments. At PG injection during the week of TAI, progesterone concentration and the proportion of cows with progesterone ≥ 1 ng/mL tended to be greater for PG-3-G than Presynch-10, and PG-3-G had more CL per cow than Presynch-10. No ovarian characteristics differed between treatments after GnRH-2, including progesterone concentration, number of CL per cow, and total luteal volume 7 days after GnRH-2. Many of the previous ovarian traits were improved in both ovular and anovular cows after PG- 3-G compared with Presynch-10. Pregnancies per AI at days 32 and 60 were only numerically greater for PG-3-G vs. Presynch-10 cows, largely because of differences detected during months without heat stress. We concluded that the PG-3-G treatment increased ovulation rate and luteal function 7 days before the onset of Ovsynch, resulting in improved follicular synchrony and predisposing potentially greater pregnancies per AI in lactating dairy cows.
Dairy Research, 2011 is known as Dairy Day, 2011
Keywords: Dairy; Luteal function; Ovulation; Presynchronization; Progesterone; Timed artificial insemination (TAI)